2021
DOI: 10.1002/ptr.7190
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the therapeutic potential of curcumin nanoformulations

Abstract: Today, due to the prevalence of various diseases such as the novel coronavirus (SARS-CoV-2), diabetes, central nervous system diseases, cancer, cardiovascular disorders, and so on, extensive studies have been conducted on therapeutic properties of natural and synthetic agents. A literature review on herbal medicine and commercial products in the global market showed that curcumin (Cur) has many therapeutic benefits compared to other natural ingredients. Despite the unique properties of Cur, its use in clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 376 publications
0
16
0
Order By: Relevance
“…Cur, a hydrophobic bioactive compound found in turmeric, offers several health benefits such as anticancer, anti-inflammatory, and antiamyloid activities . However, owing to its hydrophobic nature, Cur experiences poor cellular bioavailability and hence needs to be hooked on to a suitable carrier to effectively unravel its full therapeutic potential. , Dox is another anticancer drug from the anthracycline family, which is widely used in cancer chemotherapy. , Additionally, one of the major problems of chemotherapy using Dox is that it also affects healthy cells causing toxicity and various undesirable side effects such as cardiomyopathy that limit the maximum tolerable dose of the drug . Therefore, to avoid these limitations, the current work aims to develop a suitable carrier system for both the drugs to heighten their anticancer activity …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cur, a hydrophobic bioactive compound found in turmeric, offers several health benefits such as anticancer, anti-inflammatory, and antiamyloid activities . However, owing to its hydrophobic nature, Cur experiences poor cellular bioavailability and hence needs to be hooked on to a suitable carrier to effectively unravel its full therapeutic potential. , Dox is another anticancer drug from the anthracycline family, which is widely used in cancer chemotherapy. , Additionally, one of the major problems of chemotherapy using Dox is that it also affects healthy cells causing toxicity and various undesirable side effects such as cardiomyopathy that limit the maximum tolerable dose of the drug . Therefore, to avoid these limitations, the current work aims to develop a suitable carrier system for both the drugs to heighten their anticancer activity …”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, [1,7-bis­(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione] is a yellow-colored polyphenol plant product with several health benefits having anticancer, antiamyloid, and antioxidant properties . Despite Cur’s many potent therapeutic activities along with high-safety profile, several limitations, including poor aqueous solubility leading to low systemic bioavailability, limit its successful therapeutic translation . To address this issue, several nano- or microparticulate-based delivery agents enabling effective Cur delivery have been explored and their therapeutic potential was validated in many cellular and animal models. Additionally, numerous Cur-based self-assembled nanostructures, either in native form or in the presence of suitable co-assembling moieties, have been explored. On top of displaying potent anticancer activity, Cur has also been found to act as a photosensitizer and generate photoinduced reactive oxygen species (ROS) against cancer cells and several other disease-causing microbes .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data suggest polyphenols as potential immunomodulatory and/or antiviral agents against COVID‐19. The present virtual issue contains review addressing the potential of flavonoids, curcumin, resveratrol and silibinin in attenuating lung injury and cytokine storm associated with the disease (Derosa et al, 2021 ; Di Petrillo, Orrù, Fais, & Fantini, 2021 ; El‐Missiry, Fekri, Kesar, & Othman, 2021 ; Gour, Manhas, Bag, Gorain, & Nandi, 2021 ; Khezri, Saeedi, Mohammadamini, & Zakaryaei, 2021 ; Palit, Mukhopadhyay, & Chattopadhyay, 2021 ; Pawar & Pal, 2020 ; Santana et al, 2021 ). Studies on specific polyphenols showed that (a) kaempferol inhibited the SARS‐CoV‐2 main protease (3CLpro) (Khan et al, 2021 ), (b) oroxylin suppressed the entrance of the SARS‐CoV‐2‐spiked pseudotyped virus into ACE2 cells (Gao et al, 2021 ), (c) resveratrol inhibited the replication of SARS‐CoV‐2 in cultured Vero cells (M. Yang et al, 2021 ) and (d) silibinin interacted with SARS‐CoV‐2 main target proteins (e.g., spike protein RBD and Mpro residues) (Speciale et al, 2021 ).…”
Section: Polyphenolsmentioning
confidence: 99%
“…Finally, other review articles highlighted traditional herbs or phytochemicals for the management of cardiovascular sign and symptoms(Mohammadi Pour, Farzaei, Soleiman Dehkordi, Bishayee, & Asgary, 2021) or to overcome stress, anxiety and improve mental health associated with COVID-19(Shahrajabian, Sun, Soleymani, & Cheng, 2021).3 | POLYPHENOLSEmerging data suggest polyphenols as potential immunomodulatory and/or antiviral agents against COVID-19. The present virtual issue contains review addressing the potential of flavonoids, curcumin, resveratrol and silibinin in attenuating lung injury and cytokine storm associated with the disease(Derosa et al, 2021;Di Petrillo, Orrù, Fais, & Fantini, 2021;El-Missiry, Fekri, Kesar, & Othman, 2021;Gour, Manhas, Bag, Gorain, & Nandi, 2021;Khezri, Saeedi, Mohammadamini, & Zakaryaei, 2021;Palit, Mukhopadhyay, & Chattopadhyay, 2021;Pawar & Pal, 2020;Santana et al, 2021).…”
mentioning
confidence: 99%
“…Several types of nanomaterials have been used to improve the bioavailability of curcumin, including nanocrystals, nanopolymers, phospholipids, amphiphilic polymers, nanogel, quantum Dot, silica, gold, peptides, solid lipids, and liquid lipids for incorporation of curcumin (adapted from Khezri, Saeedi, Mohammadamini, & Zakaryaei, 2021 with permission)…”
Section: Introductionmentioning
confidence: 99%